2014
DOI: 10.7287/peerj.preprints.447v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A surge of p-values between 0.040 and 0.049 in recent decades (but negative results are increasing rapidly too)

Abstract: It is known that statistically significant results are more likely to be published than results that are not statistically significant. However, it is unclear whether negative results are disappearing from papers, and whether there exists a 'hierarchy of sciences' with the social sciences publishing more positive results than the physical sciences. Using Scopus, we conducted a search in the abstracts of papers published between 1990 and 2014, and calculated the percentage of papers reporting marginally positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…The most solid-but still observational and indirect-evidence of a growing problem with pressures to publish comes from statistical analyses of the literature. At least three independent studies suggest that, over the last few decades, abstracts of scientific papers have reported increasingly positive or statistically significant results (Pautasso, 2010;Fanelli, 2012aFanelli, , 2014de Winter and Dodou, 2014). Furthermore, at least one study noticed that positive results might be more likely to be reported by abstract of papers from academically productive areas in the United States (Fanelli, 2010a), and at least four meta-meta-analyses in the social and behavioral sciences observed that academically productive countries, and particularly the United States, might publish findings that systematically overestimate underlying effects (Doucouliagos, Laroche, and Stanley, 2005;Munafo, Attwood, and Flint, 2008;Fanelli and Ioannidis, 2013;Fanelli, Costas, and Ioannidis, 2017).…”
mentioning
confidence: 99%
“…The most solid-but still observational and indirect-evidence of a growing problem with pressures to publish comes from statistical analyses of the literature. At least three independent studies suggest that, over the last few decades, abstracts of scientific papers have reported increasingly positive or statistically significant results (Pautasso, 2010;Fanelli, 2012aFanelli, , 2014de Winter and Dodou, 2014). Furthermore, at least one study noticed that positive results might be more likely to be reported by abstract of papers from academically productive areas in the United States (Fanelli, 2010a), and at least four meta-meta-analyses in the social and behavioral sciences observed that academically productive countries, and particularly the United States, might publish findings that systematically overestimate underlying effects (Doucouliagos, Laroche, and Stanley, 2005;Munafo, Attwood, and Flint, 2008;Fanelli and Ioannidis, 2013;Fanelli, Costas, and Ioannidis, 2017).…”
mentioning
confidence: 99%